2016
DOI: 10.3390/ijerph13101013
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Japanese Articles about Suicides Involving Charcoal Burning or Hydrogen Sulfide Gas

Abstract: It is well known that certain types of media reports about suicide can result in imitative suicides. In the last two decades, Japan has experienced two suicide epidemics and the subsequent excessive media coverage of these events. However, the quality of the media suicide reports has yet to be evaluated in terms of the guidelines for media suicide coverage. Thus, the present study analyzed Japanese newspaper articles (n = 4007) on suicides by charcoal burning or hydrogen sulfide gas between 11 February 2003 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…High acute exposure to H 2 S leads to severe toxic effects, including death, with most deaths occurring at the scene of exposure . Although most H 2 S‐induced deaths are occupational‐related, suicide in confined spaces is a growing cause of death by H 2 S exposure …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High acute exposure to H 2 S leads to severe toxic effects, including death, with most deaths occurring at the scene of exposure . Although most H 2 S‐induced deaths are occupational‐related, suicide in confined spaces is a growing cause of death by H 2 S exposure …”
Section: Introductionmentioning
confidence: 99%
“…5 Although most H 2 S-induced deaths are occupational-related, [5][6][7][8] suicide in confined spaces is a growing cause of death by H 2 S exposure. 9,10 There are many sources of H 2 S in the environment, including natural discharges from volcanic activities and hot springs. 11,12 H 2 S is a contaminant of oil and natural gas and is a hazard to oil and petroleum industry workers; 4,13 in addition, sour crude oil pipeline explosion accidents have led to mass civilian casualties.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed that the methods of suicide attempts were affected by media, such as television and newspapers, 11 and media releases regarding suicide attempts due to hydrogen sulfide were thriving in Japan around 2007. 13 However, the releases settled thereafter and the detergent used to generate hydrogen sulfide was also prohibited in 2008, which would explain the decreased incidence trend of self-inflicted injury due to hydrogen sulfide. Thus, the methods of self-inflicted injuries are influenced by the discontinuation of the causative substances as well as the mass media.…”
Section: Discussionmentioning
confidence: 99%
“…As for hydrogen sulfide, the incidence of self‐inflicted injury decreased during the study period. A previous study revealed that the methods of suicide attempts were affected by media, such as television and newspapers, and media releases regarding suicide attempts due to hydrogen sulfide were thriving in Japan around 2007 . However, the releases settled thereafter and the detergent used to generate hydrogen sulfide was also prohibited in 2008, which would explain the decreased incidence trend of self‐inflicted injury due to hydrogen sulfide.…”
Section: Discussionmentioning
confidence: 99%
“…We wish to make the following three corrections to the published paper [ 1 ]. First, one of the objectives of this study was incorrect.…”
mentioning
confidence: 99%